Effect of Shenling Baizhu powder on immunity to diarrheal disease: A systematic review and meta-analysis - Chen, Qian; Xiao, Zheng; He, Qing-Ying; Zhang, Rui-Rong; Chen, Shu-Xian; Dong, Jia-Wei; Zhang, Hua; Chen, Xiao-Fan (Frontiers in Pharmacology, 2022)
Background: Diarrhea is one of the leading causes of death worldwide and is associated with immune dysfunction. The modulatory effects of Shenling Baizhu powder (SLBZS) on immune function in diarrheal disease have been validated in various animal models. However, the results of these studies have not been systematically evaluated. This study aimed to evaluate the preclinical data on SLBZS for the treatment of diarrhea from an immunological perspective. Methods: PubMed, Embase, Cochrane Library, CNKI, Wanfang Database, VIP, and Chinese Medicine Database were searched for all animal trials on SLBZS for the treatment of diarrhea published up to April 2022. Standardized mean differences (SMD) were used as effect sizes in the meta-analysis of continuous variables, including immune organs, immune cells, and immune cytokines. Subgroup analysis was performed according to animal species and disease models. The GRADE was used to assess the quality of evidence. Results: A total of 26 studies were included. Meta-analysis showed that compared to those in the model group, SLBZS significantly increased body weight (SMD=1. 54, 95% confidence interval (CI) [1.06, 2.02]), spleen mass (SMD=1.42, 95% CI [0.98, 1.87]), thymus mass (SMD=1.11, 95% CI [0.69, 1.53]), macrophage phagocytic capacity (SMD=1.07, 95% CI [0.59, 1.54]), sIgA (SMD=1.04, 95% CI [0.33, 1.74]), RBC-C3b-RR (SMD=1.16, 95% CI [0.65, 1.67]), IL-2 (SMD=1.52, 95% CI [0.89, 2.14) and decreased diarrhea scores (SMD=−1.40, 95% CI [−2.03, −0.87]), RBC-IC-RR (SMD=−1.40, 95% CI [−1.94, −0.87), and IL-8 (SMD=−2.80, 95% CI [−3.54, −2.07]). Subgroup analysis showed that SLBZS regulated TNF-α, IL-1β and IL-10 in rats and mice, and improved IL-6 and IL-10 in different diseases, with differences between subgroups (P < 0.05). Owing to heterogeneity, the reliability of the results remains to be verified. The quality of evidence was “very low”. Conclusion: SLBZS improve diarrhea symptoms by enhancing immune function. It has curative effects with differences between different species and diseases, however, because the reporting in the original studies was too unclear to be assessed, the analysis was inconclusive. For higher quality evidences, future research should pay attention to the scientific rigor of the experimental design and the completeness of the reported results.